Anthropology of Music: A Review of History, Theory, and Development - Akbar Bagaskara; Fajry Sub'haan Syah Sinaga; Alfira Audhyati; Amy Maulana (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2024)
Purpose: This article generally discusses music anthropology as a multidisciplinary field of study that explores the relationship between music, culture, and human behavior. The problem raised in this article is the lack of in-depth understanding of how music acts as a reflection, shaper, and connector of cultural dynamics, especially in the era of globalization which brings significant changes to the study of music anthropology. By exploring its historical roots in ethnomusicology to its development in the modern era, this article underlines the transformation and relevance of music studies in understanding cultural and social dynamics in various contexts, with the hope of providing theoretical and practical insights in understanding, preserving, and integrating traditional music into the modern context. Method: This research uses qualitative methods by integrating literature review, comparative analysis, and thematic exploration of key texts and case studies in the field. Data sources came from relevant books and scholarly articles to provide a comprehensive perspective. Triangulation techniques were used to validate the data through comparisons between definitions, theories and historical contexts, thus ensuring consistency of findings across approaches. Results and Discussion: The results in this study show that music anthropology, both in its classical and contemporary approaches, remains relevant as a cultural analysis tool. Conclusion: This study emphasizes the importance of interdisciplinary collaboration in understanding music, not only as an artistic expression, but also as a reflection of identity and its evolving dynamics.